Hypothesized learners' technology preferences based on learning style dimensions - Naimie, Zahra; Siraj, Saedah; Abuzaid, Rana Ahmed; Shagholi, Reihaneh (Sakarya University, 2010)
If students are demotivated, confused and look tired in class, one solution is to use new teaching styles in your class to overcome such problems. This is because learners learn in different ways such as hearing, seeing, taking notes, imagining and visualizing, among many others. The paper reports firstly, the impact of teaching and learning style preferences and their match or mismatch on learners' achievement and secondly, the proposed technology preferences for learners based on learning styles dimension. To obtain the data, the Index of Learning Styles was used together with observations and interviews to collect data. The participants were 4 lecturers and 310 students in an English major program in Iran. The findings from this study suggest that it is crucial for teachers to have knowledge about learner preferences in their classes to consider in their teaching design. The students show a positive response and higher achievement when their learning preferences and needs are accommodated by their lecturers. Based on findings, it is hypothesized that the different learning styles dimensions have their own preferences in terms of technology usage.